2011
DOI: 10.1007/3418_2011_7
|View full text |Cite
|
Sign up to set email alerts
|

Shvo’s Catalyst in Hydrogen Transfer Reactions

Abstract: This chapter reviews the use of Shvo's catalyst in various hydrogen transfer reactions and also discusses the mechanism of the hydrogen transfer. The Shvo catalyst is very mild to use since no activation by base is required in the transfer hydrogenation of ketones or imines or in the transfer dehydrogenation of alcohols and amines. The Shvo catalyst has also been used as an efficient racemization catalyst for alcohols and amines. Many applications of the racemization reaction are found in the combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 89 publications
3
54
0
Order By: Relevance
“…As shown in Scheme 2, the intermediate 26 45 was readily prepared by condensation of 1-naphthylmethylamine with cinnamaldehyde, followed by reduction. The potentially reducible double bond in 26 is well-tolerated, and Naftifine was isolated in 84% yield after the standard N-methylation reaction at 100°C.…”
Section: Acs Catalysismentioning
confidence: 99%
“…As shown in Scheme 2, the intermediate 26 45 was readily prepared by condensation of 1-naphthylmethylamine with cinnamaldehyde, followed by reduction. The potentially reducible double bond in 26 is well-tolerated, and Naftifine was isolated in 84% yield after the standard N-methylation reaction at 100°C.…”
Section: Acs Catalysismentioning
confidence: 99%
“…These results showed that it is not just the Ru metal but also the overall structure of the components of [( η 6 ‐benzene)Ru(en)Cl]PF 6 that play a crucial role in the observed high catalytic activity towards 1 . Notably, in transfer hydrogenation catalysts, ligands that have N−H bonds play a determining role particularly to help in the activation of the H source . It is evident from previous studies that among the Ru‐based catalysts explored for HCOOH to H 2 conversion or hydrogenation using HCOOH, the most active catalysts are those that have N‐based ligands .…”
Section: Resultsmentioning
confidence: 99%
“…have reported the selective hydrogenation of the aromatic ring of ketones and phenols using cyclic(amino)alkyl carbene rhodium complexes under H 2 (5 bar) . Notably, ruthenium arene complexes based on N‐donor ligands, such as ethylenediamine‐derived ligands have been identified as transfer hydrogenation catalysts, and therefore, we anticipated that these complexes could be used to achieve arene ring hydrogenation under precisely tuned reaction conditions. The reaction of the precursor, a ruthenium arene dimer, with ethylenediamine (en) in a suitable solvent led to the straightforward synthesis of cationic [( η 6 ‐arene)Ru(en)Cl] + complex .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this strategy proved problematic for the compounds of interest: Among the published procedures for amine racemization, which rely on homogeneous[8] or heterogeneous[9] metal catalysis, or thiyl radical-mediated reversible H-abstraction,[10] no method was suitable to act exclusively on the benzylisoquinoline substrates whilst leaving the berbine products untouched. For example, Shvo’s diruthenium complex[11] racemized benzylisoquinolines and berbines alike[7a] when employed under previously described reaction conditions. [8g] Raney nickel led to degradation of the complex alkaloids, whereas palladium on charcoal did not show any detectable racemization activity at all.…”
mentioning
confidence: 99%